Reducing Uncertainties of Future Global Soil Carbon Responses to Climate and Land Use Change With Emergent Constraints. Issue 10 (23rd October 2020) - Xu, Wenfang; Chang, Jinfeng; Ciais, Philippe; Guenet, Bertrand; Viovy, Nicolas; Ito, Akihiko; Reyer, Christopher P. O.; Tian, Hanqing; Shi, Hao; Frieler, Katja; Forrest, Matthew; Ostberg, Sebastian; et al.
Abstract: Soil organic carbon changes (Δ SOC ) are regulated by climate and land use change. Here, we analyze regional and global Δ SOC from 1861 to 2099 based on five terrestrial biosphere model (TBM) simulations of the Inter‐Sectoral Impact Model Intercomparison Project Phase 2b. The TBMs were driven by harmonized gridded land use change and bias‐adjusted climate forcing data from different general circulation models (GCMs) for climate scenarios RCP 2.6 and RCP 6.0. Between 2005 and the end of this century, we estimated an increase of SOC for two scenarios with large uncertainty, which is dominated by differences between TBMs. We present a new emergent constraint approach to constrain future modeled Δ SOC over natural vegetation from RCP 6.0 simulations using recent observed trends of net primary productivity as a proxy of litter inputs to soil pools. Our results showed that the uncertainties in constrained Δ SOC can be reduced in comparison with the original model ensemble, but constrained values of Δ SOC depend on the choice of a GCM and climate regions. For the reduction of the SOC density in areas where cropland expanded (Δ soc cropland expansion ) over natural vegetation as a result of land use change, the constrained Δ soc cropland expansion still features large uncertainties due to uncertain observed data. Our proposed emergent constraint approach appears to be valuable to reduce uncertainty on SOC projections, but it is limited here by the small number of models (five) and by the uncertainty in the observational data. Applications to larger ensembles from Earth System Models should be tested for the future. Key Points: The uncertainty in soil organic carbon (SOC) change is dominated by differences between model structure rather than by climate forcing Soil input changes explain most variations in projected SOC change for natural vegetation across models at global and region The effective reduction in constrained SOC change depends on climate forcing and region considered